PERANAN MASYARAKAT DALAM MENINGKATKAN PERILAKU KEAGAMAAN REMAJA MASJID AL-ANSHOR DI DESA KUBANG JAYA KECAMATAN SIAK HULU KABUPATEN KAMPAR - Suriyani Suriyani; Titi Maemunaty; Sumardi Sumardi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2021)
Abstract: Based on the background of the problem, the researcher formulates the problem in this study is how high the role of the community in improving the religious behavior of teenagers at the Al-Anshor mosque in kubang jaya village, Siak Hulu District, Kampar Regency. The purpose of this study was to determine how high the role of the community in improving the religious behavior of teenagers at the Al-Anshor mousque in kubang jaya village, Siak Hulu District, Kampar Regency. This type of research is a descriptive research with a quantitative approach. The sampling technique used is the simple jemah technique. The results and research findings of the role of society in improving the religious behavior of teenagers at the Al-Anshor Mouque in Kubang Jaya Village, Siak Hulu District, Kampar Regency are Classified as high. With the indicators of the role of the role of the community, namely 1) the role of the community as a source of information, 2) the role of the community as a facilitator, 3) the role of the community as a mentor, 4) the role of the community as a motivator.Key Words: Role, Society, Religious Behavior